Design and Tuning of Control system for blood Glucose level with artificial pancreas using harmony search Algorithm - Swaroopan, S S Pathamanabha; Pattanaik, Chinmaya Ranjan; Reddy, Shiva Shankar; Devi, E. Ahila; krishamoorthy, Sujatha (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes adds psychosocial issues to every day of life. Stress can be a major obstacle to effective glucose control. The artificial pancreas developed to control the glucose level effectively than manual injection. The closed loop controller algorithm designing procedure is proposed in this paper by considering the Bergman Minimal Model as a diabetes dynamic. Two Control strategies are designed such as proportional & Derivative controller (PD) and Internal Model Controller (IMC), and then the controller gains are optimally tuned using harmony search algorithm. The performance of controller algorithm is compared and analyzed by the closed loop simulation results.